Sudan : Final Review Under the 2002 Staff-Monitored Program and the 2003 Program; Sudan; Final Review Under the 2002 Staff-Monitored Program and the 2003 Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Executive Directors commended Sudan's efforts to bring economic policies back on track and welcomed the establishment of a mechanism to save oil export receipts arising from higher-than-programmed oil prices, but underscored the need to strengthen budget control and monitoring systems. The audit of the Sudan Petroleum Company (SPC) was completed, and netting operations by public enterprises and the private sector were abolished. The authorities' medium-term strategy aims at consolidating macroeconomic stability, sustaining economic growth, and reducing poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet